Investigation of possible predictive factors, clinical characteristics, and treatment in vascular Behçet's disease: real-life data from a single center - Abdulvahap Kahveci; Zeycan Kübra Cevval (Hitit Medical Journal)

(untitled)
Objective: The aim of this study was to investigate the phenotypes, predictive factors, and treatment approach of Behçet's patients with vascular involvement.Material and Method: This retrospective study analyzed 123 patients with Behçet's disease, 28 of whom had vascular involvement, and were followed up in our center. The study presented the vascular involvement patterns of the patients along with their clinical characteristics and comorbid conditions. The drugs usage by the patients were analyzed based on the first line and current medications, duration of medical therapy, and drug retention rate. Results: In Behçet's patients with vascular involvement, the male sex ratio was statistically higher compared to those without vascular involvement (60.7% vs 37.9%; OR=2.82(1.17-6.77); p=0.018). The frequencies of Behçet's clinical manifestations, smoking, and comorbidities were similar in both groups. The most common subtype of vascular Behçet's is deep vein thrombosis (18; 64.2%), followed by superficial thrombophlebitis (5; 17.8%), neurovascular involvement (5; 17.8%), cardio-aortic (2; 7.1%) and pulmonary arterial (2; 7.1%). Azathioprine, glucocorticoid, and cyclophosphamide are the most preferred immunosuppressives in vasculo-Behçet's. Anticoagulant therapy was initiated in 67.8% (19; 28) of the patients at the first vascular event.Conclusion: The study presented that male gender predicts vascular involvement in Behçet's disease, with deep vein thrombosis being the most common vascular subtype. Although immunosuppressive drugs represent the cornerstone of treatment for vasculo-Behçet's disease, most patients had also received anticoagulant therapy following the initial attack.